Urgensi Penerapan Akuntansi Rumah Tangga Masa Pandemi Covid-19 - Agwa Daffa Rozzaki; Yuliati Yuliati (JAS (Jurnal Akuntansi Syariah), 2022)
The emergence of covid-19 caused significant changes in the economic field. Domestic life must be more careful in managing household finances during the pandemic to control finances and avoid unwanted things. This study aims to show the application and role of household accounting during the covid-19 pandemic. This study uses a qualitative approach with a phenomenological paradigm. Data collection techniques were carried out through observation, interviews, and documentation. The informants in this study were seven housewives with a minimum educational background of a diploma in economics. The study results show that homemakers carry out financial planning by dividing current needs planned at the beginning of the month. The recording is done through books and written. Financial decisions are made together with the husband. The application of accounting in the household during the covid-19 pandemic is needed. That is because the number of needs is increasing due to the implementation of restrictions on community activities and supporting tools for health protocols. The role of accounting in the household during the pandemic helps informants plan household finances so they can control household finances wisely.